Masjid Raya Al - Mashun Medan : Ikon Arsitektur Kolonial-Islam dalam Konteks Sejarah dan Budaya Sumatera Utara - Nur Ainun Daulay (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
The Medan Grand Mosque is an example of a combination of colonial and Islamic architecture in North Sumatra. Built during the Dutch colonial rule, the mosque combines elements of distinctive Western architectural design and Islamic architectural styles, creating a unique and historic work. The existence of the Medan Grand Mosque makes it an architectural icon in the region which reflects the combination of strong colonial influences with the richness of local islamic culture. This article aims to explore the development of the architecture of this mosque as a symbol of religious and cultural identity in the midst of the colonization process, as well as its role in the history of urban development in Medan. Through this study, it is hoped that we can better understand how the Medan Grand Mosque not only functions as a place of worship, but also as a visual symbol that depicts the interaction between local traditions, Islam, and the influence of colonial architecture in North Sumatra.